Perceptive-auditive and perceptive-visual judgment in the identification of gradient productions in fricatives - de Castro Nunes, Fernanda Leitão [UNESP]; Bert, Larissa Cristina [UNESP]; de Castro Marino, Viviane Cristina [UNESP]; Fabbron, Eliana Maria Gradim [UNESP] (FapUNIFESP (SciELO), 2021)
To analyze which method of judgment, auditory-perceptual (PAJ) of audios or perceptual-visual judgment (PVJ) (ultrasound images), is more sensitive to detect gradual productions between the class of deaf coronal fricatives and check if there is a correlation between these forms of judgment. Method: Audio and video files of language ultrasound (LUS) related to the production of the words “frog” and “key”, of 11 children, between 6 and 12 years old, with atypical speech production, were selected from a bank data and edited for judgments. After instruction and prior training, 20 judges should choose, immediately upon presentation of the stimulus (auditory or visual), one of three options arranged on the computer screen. In PAJ the options were: correct, incorrect or gradient production, while in PVJ the options were images corresponding to the production of [s], [∫] or undifferentiated. The presentation time of the stimuli and the reaction time were automatically controlled by the PERCEVAL software. Results: PVJ provided a higher percentage of identification of gradient stimuli and a shorter reaction time in performing the task compared to PAJ, both statistically significant. Spearman’s correlation test did not show statistical significance between PAJ and PVJ responses, nor for reaction time. Conclusion: PVJ using US images proved to be the most sensitive method for detecting gradient production in the production of fricatives [s] and [∫], and can be used as a complementary method to PAJ in speech analysis.
Julgamento perceptivo-auditivo e perceptivo-visual na identificação de produções gradientes em fricativas
Keywords: Auditory Perception; Fricatives; Portuguese Language; Ultrasonography; Visual Perception